2018
DOI: 10.3233/npm-181711
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with long-term mechanical ventilation in extremely preterm infants

Abstract: In this cohort of infants born at <27 weeks gestation 35% were on long term IPPV. There are identifiable factors known on admission and occurring during the NICU stay that are associated with long-term IPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…It is associated with prolonged exposure to MV 6 , and the association between PH and BPD is related to both its pathogenesis (similarly associated to complications of prematurity) and secondary PH development in BPD 24 . There was no difference between groups regarding PDA, NEC, use of VAD, chorioamnionitis and maternal use of tobacco, unlike other studies about both prolonged time under MV and higher severity of BPD 6,20 , which might have occurred due to the relatively small sample size.…”
Section: Discussioncontrasting
confidence: 76%
“…It is associated with prolonged exposure to MV 6 , and the association between PH and BPD is related to both its pathogenesis (similarly associated to complications of prematurity) and secondary PH development in BPD 24 . There was no difference between groups regarding PDA, NEC, use of VAD, chorioamnionitis and maternal use of tobacco, unlike other studies about both prolonged time under MV and higher severity of BPD 6,20 , which might have occurred due to the relatively small sample size.…”
Section: Discussioncontrasting
confidence: 76%
“…It is associated with prolonged exposure to MV 6 , and the association between PH and BPD is related to both its pathogenesis (similarly associated to complications of prematurity) and secondary PH development in BPD [24]. There was no difference between groups regarding PDA, NEC, use of VAD, chorioamnionitis and maternal use of tobacco, unlike other studies about both prolonged time under MV and higher severity of BPD [6,20], which might have occurred due to the relatively small sample size. Additionally, a reasonable number of BPD patients did not survive until they completed 36 weeks PMA, which may also have contributed to this difference in outcomes.…”
Section: Discussionmentioning
confidence: 66%
“…Recent studies have enhanced the harms of exposure for extremely preterm infants to MV for long periods of time. Yossef et al observed that a group of extremely premature infants that were submitted to more than 56 days of MV had a higher incidence of moderate to severe BPD [20]. Choi et al found an almost three-fold increase in the risk of mortality of extremely low birth weight preterm infants who required MV for 15 to 28 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yossef et al included 210 patients born at < 27 weeks from 2005 to 2011. They further found that long-term intermittent positive pressure ventilation patients were born earlier and had lower birth weight 20 . Markestad et al performed a prospective observational study of 636 infants with a GA of 22–27 weeks or a birth weight of 500–999 g. For the survivors, days of invasive MV decreased from a median of 37 days to 3 days, and the proportion in need of oxygen at 36 weeks’ PMA decreased from 67 to 26% at 23 and 27 weeks’ GA, respectively 21 .…”
Section: Discussionmentioning
confidence: 95%